THR PIG WITH GREEN SPORTS AND OTHERS STORIES - Blyton, Enid. (Blyton, Enid., 2005)
Retells the Old Testament story in which the baby Moses is placed in a basket among tall reeds along the river, found by an Egyptian princess, and saved from being killed.